Perkembangan Bisnis Pariwisata Di Kota Parapat Ditinjau Dari Perspektif Pembangunan Danau Toba Sebagai “Monaco Of Asia” - Nalom Siagian; Steven Jordan Siallagan (Jurnal Ilmu Sosial Dan Politik, 2022)
This study aims to determine the development of the tourism business in the area of ​​Lake Toba, Parapat City, Girsang Sipanganbolon District in terms of the perspective of developing Lake Toba as an international class "Monaco of Asia". The type of research used is descriptive with a qualitative approach. Data collection was carried out using observation, interview and documentation techniques. The results show that the development of Lake Toba as a tourism business in Parapat City has increased, such as in the Hospitality and Restaurant sector. In developing the tourism potential of Lake Toba, Parapat City has strengths, weaknesses, opportunities and challenges. Its greatest strength is natural tourism, artificial tourism, and also cultural tourism. Weaknesses that are owned are human resources, facilities and infrastructure that still need to be addressed, and limited capital owned. For this reason, it is necessary to have good cooperation between the government and the local community so that the development of the tourism business in Parapat City can be improved even better.